VOT Patterns in the Acquisition of Third Language Phonology - Wrembel, Magdalena (My University, 2014)
The paper aims at investigating the phenomenon of cross-linguistic influence in the acquisition of third language phonology by exploring the interaction between three phonological systems of multilingual subjects based on their productions of voice onset time patterns. It presents the results of two parallel studies involving different language combinations; (1) L1 Polish, L2 English, and L3 French; (2) L1 Polish, L2 English, and L3 German.. The participants (N=64) were recorded reading lists of words in carrier phrases in the three respective languages (L1, L2 and L3) and the recordings were subsequently analyzed for the degree of aspiration of voiceless stops in stressed onset positions. The results revealed unique interlanguage VOT patterns as the multilingual subjects contrasted between VOT length in all three language systems. The L3 values corresponded to compromise VOT values and were intermediate between the L1 and L2 mean VOT. The findings corroborated the co-existence of the L1 and L2 effect, and substantiated the assumption of a combined cross-linguistic influence in L3 acquisition.
Keywords: VOT; acquisition of phonology; L3